Petri net modelling and analysis of a supply chain network - Liu, Haohang (2017)
Given that supply chain networks are becoming more inter-connected and complex, it becomes crucial to study their strengths and limitations, especially vulnerabilities to disruptions. These reasons motivated this Final Year Project (FYP) to create a prototype Petri Net (PN) model which can incorporate internal manufacturing capabilities, deal with more than one product, and include different operational policies, such as weighted procurement policy from different suppliers and proportional fulfilment policy for different customers. The Petri Net technique is an ideal modelling tool for its ability to model events in a supply chain and its direct visual display of the elements involved. The PN model was verified against detailed manual calculation. The modular approach, which breaks down supply chain into various functions such as replenishment and procurement, allows any supply chain with any number of supply chain entities and complex bill of materials to be constructed. The possible types of disruptions this Petri Net can model and analyse are also discussed. Examples of such disruptions include inventory shortfalls caused by fire and transportation delays caused by severe weather conditions.